2008
DOI: 10.1007/s00415-008-0707-z
|View full text |Cite
|
Sign up to set email alerts
|

“Pseudodominant inheritance” of ataxia with ocular apraxia type 2 (AOA2)

Abstract: Ataxia with ocular apraxia type 2 (AOA2) is an autosomal recessive, early onset ataxia caused by mutations in the senataxin (SETX) gene. Ocular apraxia and increased levels of alpha-fetoprotein are characteristic but not obligate markers of the disease. AOA2 is allelic with ALS4, a motor neuron disorder of early onset and autosomal dominant inheritance. We observed a two generation family with ataxia which started at age 14 and 17 in two sibs and at age 23 in their paternal uncle.Oculomotor disturbances includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…26 Sensorimotor axonopathy has been reported in AOA2 by a number of investigators. 3,4,6,11,12,15,22,27 However, as neither electromyographic (EMG) recordings of proximal muscles nor conduction studies of nerves of the proximal segments of the limbs were mentioned in those studies, and as somatosensory evoked potentials were documented only once, 4 it appears those studies did not aim to distinguish axonopathy from neuronopathy.…”
Section: Discussionmentioning
confidence: 97%
“…26 Sensorimotor axonopathy has been reported in AOA2 by a number of investigators. 3,4,6,11,12,15,22,27 However, as neither electromyographic (EMG) recordings of proximal muscles nor conduction studies of nerves of the proximal segments of the limbs were mentioned in those studies, and as somatosensory evoked potentials were documented only once, 4 it appears those studies did not aim to distinguish axonopathy from neuronopathy.…”
Section: Discussionmentioning
confidence: 97%
“…AOA2 has been associated with various alterations that cause frameshift, nonsense, and missense mutations [15]. The missense mutation presented in this manuscript, c.7331GNA(p.Arg2444Hist), has been described previously [16,23] and consists of a homozygous substitution of guanine for adenine at position 7331, in exon 26 of the SETX gene.…”
Section: Discussionmentioning
confidence: 98%
“…Sensorimotor axonopathies [3,4,6,7,[13][14][15][16] and neuronopathies [17] have been reported in AOA2, although some authors have reported isolated sensory involvement in AOA2, on clinical grounds alone [2,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disorder was first described in Japanese [11] and Pakistani [8] families, later reports included six families from different Mediterranean areas and the West Indies [5], ten French-Canadian families known as the Quebec cluster [3], four families from Italy [2], one German [10] and one Cypriot family [9]. Although included in the disease name, oculomotor apraxia is not obligatory for diagnosis of AOA2 and was absent in our patient [3][4][5].…”
Section: Sirsmentioning
confidence: 90%